2013
DOI: 10.1242/dev.089326
|View full text |Cite
|
Sign up to set email alerts
|

Defining skeletal muscle resident progenitors and their cell fate potentials

Abstract: SUMMARYThe satellite cell is the major tissue-resident stem cell underlying muscle regeneration; however, multiple non-satellite myogenic progenitors as well as non-myogenic populations that support the muscle regenerative process have been identified. PW1 is expressed in satellite cells as well as in a subset of interstitial cells with myogenic potential termed PICs (PW1+ interstitial cells). Microarray profiling revealed that PICs express a broad range of genes common to mesenchymal stem cells, whereas satel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 50 publications
8
137
2
Order By: Relevance
“…+ Cells Are Present in Perivascular and Parenchymal Zones, Express Progenitor and Pericyte Markers, and Differentiate Into SMC PW1 expression was found to identify adult stem and progenitor cells in multiple organs 14,15,20 although previous studies did not report on the expression in the lung. PW1 protein expression was detected by immunofluorescence in cells located in parenchymal and perivascular spaces, near small nonmuscularized and muscularized vessels ( Figure 1A and 1B).…”
Section: Mouse Pulmonary Pw1mentioning
confidence: 95%
See 1 more Smart Citation
“…+ Cells Are Present in Perivascular and Parenchymal Zones, Express Progenitor and Pericyte Markers, and Differentiate Into SMC PW1 expression was found to identify adult stem and progenitor cells in multiple organs 14,15,20 although previous studies did not report on the expression in the lung. PW1 protein expression was detected by immunofluorescence in cells located in parenchymal and perivascular spaces, near small nonmuscularized and muscularized vessels ( Figure 1A and 1B).…”
Section: Mouse Pulmonary Pw1mentioning
confidence: 95%
“…14,15 These PW1-expressing cells were found in multiple adult tissues including skin, gut, BM, and the central nervous system.…”
mentioning
confidence: 99%
“…These two courses of the SCs population relate to their Myf5 transcription factor expression: the dominant population Pax7 interstitial cells). Further details on intrinsic regenerative populations associated to skeletal muscle and SCs origins and dynamics can be found elsewhere [23][24][25][26][27].…”
Section: Skeletal Muscle Structure and Intrinsic Healing Mechanismsmentioning
confidence: 99%
“…In subsequent decades, Mauro's hypothesis proved true, and a number of studies demonstrated that SCs are the key mediators of post-natal skeletal muscle growth, homeostasis and repair [2][3][4] . The core functions of SCs are the repair of damaged muscle fibers and the maintenance of an adequate pool of stem cells.…”
Section: Satellite Cellsmentioning
confidence: 99%